The Narration of Anecdote The Pathology of the Narration Theory:A Case Study of Vladimir Propp's Theory of Morphology - Masroureh Mokhtari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Narratology is a new approach to study fiction, and it tries to find out the structure of the story, discover the narrative language, the system governing narrative types, and their structures. In the recent decade, the Narration Theory has received a considerable attention in studying different kinds of literary genres. The present research is a case study with the suggested model in the form of 31 functions and 7 characters presented in the book named "Morphology of Fairy Tales" by Vladimir Propp; the conducted studeis such as theses and articles with an analytic approach have been conducted and those damages which have been caused by using this theory to the conducted studies have been investigated considering the compatibility or incompatibility of the theory with the text, misunderstanding of narration, and so on. The result of the research indicates that although Propp's theory in the field of narrative texts holding Folkloric infrastructure has been one of the main attempts to understand the usage of functions in fiction, it is necessary to make some changes in the suggested model regarding the text and the requirements of studied society.  It can be concluded that customizing this theory and other similar theories in Narratology is a necessity to do research on narrative fiction texts, and without taking these considerations into accounts, most of the conducted studies are ambiguous regarding the validity of their results.